Use of technologies for the production of texts with academic originality - Cantoral, E.M. (2019)
This innovation entitled use of technologies for production of texts with academic originality, aims to develop in student’s the ability to produce texts respecting sources consulting to create their own texts and use technology as a support in regulating it’s the originality academic. The methodology used was request the student to present the academic works through an anti-plagiarism software with free access delivery. The results showed a change of attitude in the students when making use of the platform, they began to use citations for parts of the copied texts and they reconstructed their own words to which no reference was make before.